2012
DOI: 10.1016/j.biopsych.2011.11.018
|View full text |Cite
|
Sign up to set email alerts
|

The Stress-Induced Cytokine Interleukin-6 Decreases the Inhibition/Excitation Ratio in the Rat Temporal Cortex via Trans-Signaling

Abstract: Background Although it is known that stress elevates the levels of pro-inflammatory cytokines and promotes hyper-excitable central conditions, a causal relationship between these two factors has not yet been identified. Recent studies suggest that increases in interleukin 6 (IL-6) levels are specifically associated with stress. We hypothesized that IL-6 acutely and directly induces cortical hyper-excitability by altering the balance between synaptic excitation and inhibition. Methods We used patch-clamp to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 77 publications
5
61
1
Order By: Relevance
“…We employ bolus application of neuromodulators upstream of the recording electrode in the slice perfusate to simulate phasic release of neuromodulators known to be associated with salient environmental stimuli that are necessary for transient modulation of executive functions [13,22]. Our results show that systemic LPS injection, not only reduces cortical inhibition, consistent with prior studies [7,17,20], but also alters the temporal dynamics of ACh-neuromodulation that is associated with increased ACh-E activity and impairment in memory performance. Although AChneuromodulation is affected, NE and 5-HT effects were not altered, consistent with the lack of a behavioral effect on anxiety and despair assessments.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We employ bolus application of neuromodulators upstream of the recording electrode in the slice perfusate to simulate phasic release of neuromodulators known to be associated with salient environmental stimuli that are necessary for transient modulation of executive functions [13,22]. Our results show that systemic LPS injection, not only reduces cortical inhibition, consistent with prior studies [7,17,20], but also alters the temporal dynamics of ACh-neuromodulation that is associated with increased ACh-E activity and impairment in memory performance. Although AChneuromodulation is affected, NE and 5-HT effects were not altered, consistent with the lack of a behavioral effect on anxiety and despair assessments.…”
Section: Discussionsupporting
confidence: 90%
“…The acute prostaglandin-mediated behavioral response typically subsides within 2-3 days [8] while systemic inflammation subsides within 7-10 days [16]. However, inflammatory cytokine-mediated increases in brain excitation [7,20] may be much longer-lasting. Additionally, inflammatory signaling pathways, reactive oxygen species and stress are all known to increase monoamine oxidase-A (MAO-A) and acetylcholinesterase (ACh-E) activity in vitro [4,11,14].…”
Section: Lipopolysaccharidementioning
confidence: 98%
“…Intracranial infusions of IL-6 91 or administration of IL-1b 92, 93 into the hippocampus increase depression associated behavior and reduces neurogenesis, whereas infusion of IL-1b 93 and IL-6 91 antibodies, or genetic deletion of IL-6 94 , blocks the depressive-like effects induced by CMS. Cytokines can act on serotonin neurons through the kynurenine pathway and tryptophan catabolites 95, 96 as well as directly on glutamatergic neurons in the frontal cortex 97 and hippocampus 98 to alter synaptic plasticity. Danger signals also act directly on nerve cells that express the TLR4 receptor to alter neurogenesis in the hippocampus 99 , a process important for depression and antidepressant responses 100 Lastly, cytokines/chemokines can activate a microglia-dependent phagocytic process that engulfs and clears excitatory synapses altering synaptic transmission and behavior 101 .…”
Section: Interface Between Peripheral Immune Cells and Brainmentioning
confidence: 99%
“…In a study by Levy et al, mice treated with intraventricular injections of IL-6 were monitored for cortical seizure activity and they displayed significantly more seizure-like activity when compared to control mice (Levy et al, 2015). Single cell recordings performed in cortical rat slice preparations have shown that IL-6 application causes a decrease in evoked inhibitory post synaptic current amplitude without changing evoked excitatory post synaptic current amplitudes (Garcia-Oscos et al, 2012); suggesting IL-6 can drive neurons into a more excitable state. Moreover, transgenic mice with increased astrocytic production of IL-6 driven by GFAP (GFAP-IL6) have been found to be significantly more sensitive to NMDA- and KA-induced seizures (Campbell et al, 1993; Samland et al, 2003).…”
Section: Seizures and Epilepsymentioning
confidence: 99%